2006
DOI: 10.1177/02711214060260010401
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perspectives on the Use of Assistive Technology for Infants and Toddlers With Disabilities

Abstract: A random sample of 967 early intervention providers in 33 different states completed a telephone survey that was conducted with computer-assisted telephone interview technology. The survey solicited information about the service providers' views of assistive technology (AT) for infants and toddlers with disabilities. In particular, questions elicited information regarding the use of AT, factors important to making decisions about AT, access to resources (e.g., funding, lending libraries), and provider training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Lack of assistive technology knowledge and skills are not a novel discovery. Previous researchers (Ashton et al, 2005;Bausch and Hasselbring, 2004;Parette et al, 2006;Smith and Kelley, 2007;Wilcox et al, 2006 ) concluded that teachers were not confident in using assistive technology due to lack of knowledge and training in this area. Knowledge and skills of using assistive technology essential for general education and special education teachers in equal measure.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of assistive technology knowledge and skills are not a novel discovery. Previous researchers (Ashton et al, 2005;Bausch and Hasselbring, 2004;Parette et al, 2006;Smith and Kelley, 2007;Wilcox et al, 2006 ) concluded that teachers were not confident in using assistive technology due to lack of knowledge and training in this area. Knowledge and skills of using assistive technology essential for general education and special education teachers in equal measure.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the studies indicated that there was a strong relationship between the type of technology used and its contribution to children's development. , 2006;Korat & Shamir, 2007;Marsh, 2004;Segers & Verhoeven, 2003;Segers & Verhoeven, 2005;Skouteris & Kelly, 2006;Wang & Ching, 2003;Wilcox, Guimond, Campbell, & Moore, 2006). Only four studies showing the negative results of technology usage on young children's development (Bacigalupa, 2005;Lau et al 2005;Luckin, Connolly, Plowman, & Airey, 2003;Plowman & Stephen, 2007).…”
Section: Types Of Technologymentioning
confidence: 99%
“…Eight studies (40 %) were carried out before 2006 (Bacigalupa, 2005;Kent & Facer, 2004;Lau et al, 2005;Luckin et al, 2003;Marsh, 2004;Segers & Verhoeven, 2003;Segers & Verhoeven, 2005;Wang & Ching, 2003). In 2006, seven studies (35 %) were carried out (Buckleitner, 2006;Ching et al, 2006;Chung & Walsh, 2006;Espinosa et al, 2006;Hinde & Wolery, 2006;Skouteris & Kelly, 2006;Wilcox et al, 2006). Five technologyrelated studies (25 %) were after 2006(Baroody et al, 2009Korat & Shamir, 2007;Plowman & Stephen, 2007;Stephen et al, 2008;Zevenbergen & Logan, 2008).…”
Section: Table 3: the Positive Effects Of Technology On Children's DImentioning
confidence: 99%
“…The knowledge and experience of caregivers are identified as essential factors to successful AT-use as these may influence their willingness to use AT, their beliefs in its possibilities, and the skills to use AT [e.g. 1, [29][30][31][32]. One could ask if increased knowledge and experience may impact the effect of first-and second-order barriers.…”
Section: Introductionmentioning
confidence: 99%